Proteome-Wide Analysis of Lysine 2-Hydroxyisobutyrylation in the Phytopathogenic Fungus Botrytis cinerea - Xu, Yang; Li, Xiaoxia; Liang, Wenxing; Liu, Mengjie (Frontiers in Microbiology, 2020)
Posttranslational modifications (PTMs) of the whole proteome have become a hot topic in the research field of epigenetics, and an increasing number of PTM types have been identified and shown to play significant roles in different cellular processes. Protein lysine 2-hydroxyisobutyrylation (Khib) is a newly detected PTM, and the 2-hydroxyisobutyrylome has been identified in several species. Botrytis cinerea is rec-ognized as one of the most destructive pathogens due to its broad host distribution and very large economic losses; thus the many aspects of its pathogenesis have been continuously studied. However, distribution and function of Khib in this phytopatho-genic fungus are not clear. In this study, a proteome-wide analysis of Khib in B. cinerea was performed, and 5,398 Khib sites on 1,181 proteins were identified. Bioinformatics analysis showed that the 2-hydroxyisobutyrylome in B. cinerea contains both con-served proteins and novel proteins when compared with Khib proteins in other species. Functional classification, functional enrichment and protein interaction network anal-yses showed that Khib proteins are widely distributed in cellular compartments and involved in diverse cellular processes. Significantly, 27 proteins involved in different aspects of regulating the pathogenicity of B. cinerea were detected as Khib proteins. Our results provide a comprehensive view of the 2-hydroxyisobutyrylome and lay a foundation for further studying the regulatory mechanism of Khib in both B. cinerea and other plant pathogens.